Պարույր Սևակի բանագիտական հայացքները - Արմեն Սարգսյան (ՀՀ ԳԱԱ հրատ.)
Фольклороведческие взгляды П. Севака начинают формироваться уже в период его учебы в Ереванском университете, а затем в Москве, в книге “Абовян и народная словесность”, в статье “Поэзия Варужана”. Более четко и глубоко они проявляются в работах Севака о средневековых поэтах Нарекаци, Кучаке, Саят-Нове, также в статье “За и против первооснов реализма” и в интервью “Что, как и каким образом?” Поэт “тонратнаин-сказочной” литературе противопоставляет симфоническую, многоголосную и глубокомысленную литературу, созвучную новым временам. The objective of the present paper is to reveal Paruyr Sevak’s views on folk-lore study in the early period of his literary activities. The poet’s views on folk-lore study were already formulated in his review of the book “Abovyan and Folk-lore” and in the article “Varujan’s Poetry”. Sevak’s views on folk-lore study are more deeply and distinctly expressed in his works devoted to medieval poets Narekatsy, Kuchak and Sayat-Nova, as well as in the article “For and Against the Principles of Realism” and in the interview “What and How?”. The poet opposes to the “fantastic” literature the symphonic, polyphonic and deeply perceived literature, which is in tune with the new times.
Keywords: Literature; Language and Literature